Methods for extracting markers from Spore killer strains of Neurospora crassa - D. D. Perkins (Fungal Genetics Reports, 1996)
A mutant gene is most simply transferred from killer to nonkiller by crossing a marked killer strain x Sk sensitive acr-2R, plating ascospores on medium supplemented with acriflavine, and recovering mutant progeny among the acriflavine-resistant colonies, which are nonkillers that presumably originated from rare heterozygous or heterokaryotic ascospores.